Optimalisasi Penilaian Pajak Korporasi untuk Meningkatkan Penerimaan Pendapatan Negara - Yayat Sudrajat; Rahmat Heryat Furqon; Yana Sahyana; Dadang Suwanda (Ekonomis: Journal of Economics and Business, 2022)
Taxes are a source of enormous potential revenue. A country's collection system, both Self Assessment and Official Assessment, will greatly affect the increase in government funding receipts. One type of tax revenue is from a test assessment of corporate taxpayer compliance which will affect the assessment of tax objects objectively and professionally in accordance with assessment standards and tax provisions so that state revenues are expected to increase. The research methodology used is based on the type of qualitative research. One of the advantages of this method is that researchers can find an in-depth understanding or interpretation of a phenomenon that is happening. In addition, descriptive qualitative research is carried out by examining the literature or literature studies that focus on explaining the research results obtained, as well as by collecting data by in-depth interviews. The results of the study indicate that it is necessary to conduct a business assessment to determine the value of an object of assessment in an objective and professional manner according to assessment standards and tax regulations on going concern, including business ownership interest, transactions and everything that affects on the value of corporations, to increase state revenue because currently its implementation is not optimal.